Relasi Kuasa antara Muslim Ortodoks dan Penghayat Kaweruh Kamanungsan di Banyuwangi dalam Perspektif Ideological State Apparatus Louis Althusser - Masrifah, Lia Hilyatul (Religió: Jurnal Studi Agama-agama, 2016)
This article attempts to scrutinize the relation between Orthodox Muslim and the followers of Kaweruh Kamanungsan in Sedoyo, Banyuwangi, East Java. These two religious groups that have two different and opposite ideological perspectives, apparently, have influenced cultural and structural agencies in the village. Having utilized Althusser’s Ideological State Apparatus, the elites of these groups are competing each other to introduce their own ideologies into social institutions like religion, education, family, and legal instruments. As a result, village structures are divided into Muslim and Kaweruh Kamanungsan groups. Evidently, Muslim groups who have vertical link into government and horizontal one into society succeeded to eliminate “deviant” local tradition groups. However, Kaweruh Kamanungsan, as one of local tradition in this village, has survived from the proselytizing program and has successfully built a bridge to eliminate the gap between religious and cultural differences in society.